A wide input bandwidth 7-bit 300-MSample - Yunchu Li (IEEE Journal of solid state circuits)
A 7-bit Nyquist folding and interpolating analog-to-digital converter (ADC) that converts at 300 MSamples/s is presented. Using current-mode signal processing techniques for analog preprocessing and a front-end sample-and-hold, the proposed 7-bit folding and interpolating ADC yields a wide input bandwidth up to 60 MHz with six effective number of bits. The ADC consumes 200 mW from a 3.3-V power supply. The chip occupies 1.2 mm2 active area, fabricated in 0.35-μm CMOS.